The experimental investigation of effects of multiple parameters on the formability of the DC01 sheet metal - Gürün, Hakan (Strojniški vestnik, 2015)
The formability of sheet metal materials through the deep drawing process is affected by various parameters, such as die chamber pressure, die radius and sheet thickness, all of which directly influence the product's quality. This paper investigates the formability of the DC01 sheet metal material. DC01 is a carbon steel sheet, which has a wide range of usages from the automotive industry to the manufacture of radiators by means of hydro-mechanical and conventional deep deep drawing methods. This study, for the first time, empirically investigates the effects of die chamber pressure, die radius and sheet thickness on the formability of DC01 sheet metal material through hydro-mechanical and conventional deep deep drawing methods. The study also helps to determine the forming parameters for this material. With regard to the hydro-mechanical deep drawing process, the drawing ratio increased from 2.16 to 2.33, solely due to an increase in die chamber pressure. The results of the experiment revealed suitable forming parameters through hydro-mechanical and conventional deep drawing methods for samples of DC01 material having a cylindrical geometry.
Keywords: hidroforming; hidromehanski globoki vlek; konvencionalni globoki vlek; preoblikovanje pločevine